Volume 5: 26th Design for Manufacturing and the Life Cycle Conference (DFMLC) 2021
DOI: 10.1115/detc2021-69629
|View full text |Cite
|
Sign up to set email alerts
|

Design for Product Circularity: Circular Economy Indicators With Tools Mapped Along the Engineering Design Process

Abstract: Monitoring the circularity potential of products and materials is key to ensure environmental savings and economic profitability of circular economy loops, such as reuse, remanufacturing, or recycling. The choices and decisions made during the product design phase have a major influence and impact on the circularity performance of products. While numerous indicators and tools have been recently developed to assess, manage, and accelerate the transition to a more circular economy, their application and usabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The list below comprises the existing and freely available circularity assessment tools currently available at the micro level, i.e., tools which can be applicable to organizations, products, or projects, the latter being the focus of this work: From the literature review, no specific circularity assessment tools were found for application in road infrastructure projects; however, at least three sustainability assessment tools for infrastructure were found to exist, so they were also included in the review. These three reviewed tools are mentioned below: Under the idea of defining ideal requirements or characteristics to design a framework with the aim of measuring and/or evaluating and monitoring the circularity of the built environment, the revised tools are subjected to a comparative analysis based on the pyramid of desired characteristics to design a circularity measurement framework proposed by Saidani [74]. This pyramid considers five cornerstones for a CE measurement framework:…”
Section: Circularity Assessment Toolsmentioning
confidence: 99%
“…The list below comprises the existing and freely available circularity assessment tools currently available at the micro level, i.e., tools which can be applicable to organizations, products, or projects, the latter being the focus of this work: From the literature review, no specific circularity assessment tools were found for application in road infrastructure projects; however, at least three sustainability assessment tools for infrastructure were found to exist, so they were also included in the review. These three reviewed tools are mentioned below: Under the idea of defining ideal requirements or characteristics to design a framework with the aim of measuring and/or evaluating and monitoring the circularity of the built environment, the revised tools are subjected to a comparative analysis based on the pyramid of desired characteristics to design a circularity measurement framework proposed by Saidani [74]. This pyramid considers five cornerstones for a CE measurement framework:…”
Section: Circularity Assessment Toolsmentioning
confidence: 99%